Ung Dansk Kunsts Tapeserie, 1969: Lydspor af Eks-skolens attituderelativisme - Magnus Kaslov (Periskop – Forum for kunsthistorisk debat, 2025)
Ten audio works by artists associated with the Danish artist group Eks-skolen were released in 1969. Despite the fact that most of the artists have since been established as central characters in the Danish art scene, the sound pieces have disappeared out of earshot and remained uncollected by museums. In the course of a years-long search, six of the ten soundworks have been located and digitized. This article discusses how the works have remained unheard – and largely unheard of – in Danish art history and seeks to counter this by describing the six found works by Erik Thygesen (1941-1992), Bjørn Nørgaard (1947- ), Stig Brøgger (1941-2021), Poul Gernes (1925-1996), Henning Christiansen (1932-2008), and Joseph Beuys (1921-1986) in relation to the individual artists’ practices and the collective thoughts on so-called attitude relativism [attituderelativisme] developing in Eks-skolen at the time, and described in the manifesto-like periodical ta’ (1967-1968). These artworks engage with the social conventions of formats, rather than narrowing in on medium-specific essentials.